Leveraging Digital Learning Tools to Boost Student Motivation: A Study Using Univariate and Bivariate Analysis on Enhancing Engagement in Elementary Science and Social Studies - Wigati, Evia Nursanti; Lidyasari, Aprilia Tina; Adi, Banu Setyo (Mimbar Sekolah Dasar, 2025)
The integration of digital learning tools is increasingly shaping modern education, driven by technological advancements and the need for interactive teaching methods. These tools are believed to enhance student engagement and motivation, particularly in foundational subjects like Science and Social Studies. This study examines the relationship between digital learning tools and student motivation among Grade 3 learners, employing a non-experimental, cross-sectional survey design with 30 participants from two elementary schools. The research assesses two key variables: the use of digital learning tools and student motivation levels, measured through a standardized motivation questionnaire, classroom records, and teacher reports. Findings reveal a statistically significant association between digital tool usage and higher motivation levels (p = 0.006). The odds ratio of 4 suggests that students using digital tools are four times more likely to exhibit high motivation than those relying on traditional methods. These results highlight the potential of digital learning tools to enhance student engagement and underscore the need for their integration into educational practices. However, the study acknowledges its limitations, such as its cross-sectional design. Despite this, the findings provide valuable insights for educators and policymakers seeking to improve teaching strategies and student outcomes through technology integration in elementary education.